2004
DOI: 10.1128/iai.72.5.2484-2493.2004
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Lipoprotein NlpI in the Virulence of Adherent Invasive Escherichia coli Strain LF82 Isolated from a Patient with Crohn's Disease

Abstract: Escherichia coli strain LF82 recovered from a chronic lesion of a patient with Crohn's disease (CD) is able to adhere to and invade cultured intestinal epithelial cells and to replicate within macrophages. One mutant selected for its impaired ability to invade epithelial cells had an insertion of a Tn phoA transposon within the nlpI gene encoding the lipoprotein NlpI. A NlpI-negative isogenic mutant showed a 35-fold decrease in its ability to adhere to and a 45-fold decrease in its ability to invade Intestine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…YhjH is an EAL domain c-di-GMP phosphodiesterase required for the breakdown of the novel second messenger c-di-GMP (41). We show that it is the c-di-GMP phosphodiesterase activity of YhjH, and not any other property of YhjH, that was critical, because we were able to replace YhjH with an alternative EAL domain, c-di-GMP phosphodiesterase YahA (43), or achieve the same phenotype by deleting the diguanylate cyclase gene yaiC (37). We demonstrate that overexpressed YaiC did not change the adhesion and invasion abilities of the LF82 strain, which indicates that physiological amounts of the diguanylate cyclase are sufficient for its activity.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…YhjH is an EAL domain c-di-GMP phosphodiesterase required for the breakdown of the novel second messenger c-di-GMP (41). We show that it is the c-di-GMP phosphodiesterase activity of YhjH, and not any other property of YhjH, that was critical, because we were able to replace YhjH with an alternative EAL domain, c-di-GMP phosphodiesterase YahA (43), or achieve the same phenotype by deleting the diguanylate cyclase gene yaiC (37). We demonstrate that overexpressed YaiC did not change the adhesion and invasion abilities of the LF82 strain, which indicates that physiological amounts of the diguanylate cyclase are sufficient for its activity.…”
Section: Discussionmentioning
confidence: 86%
“…Decreased Adhesion and Invasion of the ⌬flhD and ⌬fliA Mutants Is a Consequence of Lowered Levels of Type 1 Pili-The decrease in the ability to adhere to and to invade epithelial cells has been observed in nonflagellated mutants of strain LF82 and was attributed to lower type 1 pili levels (32,37). We therefore analyzed expression of type 1 pili in the LF82-⌬flhD and LF82-⌬fliA mutants by monitoring bacterial aggregation of yeast cells, which occurs as a result of pili binding to D-mannose residues located at the yeast surface.…”
Section: Flhd 2 C 2 and Flia Play Key Roles In Interactions Of Aiec Smentioning
confidence: 99%
“…Flagella also play a direct role in the adhesion and invasion processes of AIEC strain LF82 via motility and an indirect role in the interaction between bacteria and epithelial cells by down-regulating the expression of type 1 pili (3). In addition, the lipoprotein NlpI, which is probably located in the inner membrane, is thought to operate in a regulatory pathway involved in the synthesis of flagella, type 1 pili, and other virulence factors yet to be identified (4).…”
Section: Adherent-invasivementioning
confidence: 99%
“…Some progress has been made with the identification of genes responsible for adherence to and invasion of epithelial cells, but these studies have only been conducted in one ileal isolate from Crohn's disease, LF82 (Barnich et al, 2004;Rolhion et al, 2005Rolhion et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In both Crohn's disease and colon cancer, we (Martin et al, 2004) and others (Swidsinski et al, 1998) have found mucosa-associated E. coli that resisted gentamicin treatment of the mucosal samples and were therefore presumed to be intracellular. It has been demonstrated that Crohn's disease-associated E. coli adhere to and invade epithelial cell lines in vitro (Darfeuille- Michaud et al, 2004;Martin et al, 2004) and replicate inside macrophage phagolysosomes (Bringer et al, 2006), with resulting giant cell formation (Meconi et al, 2007). It has been reported (Kotlowski et al, 2007) that these adherent and invasive E. coli (AIEC) belong to phylogenetic groups B2 and D (Clermont et al, 2000), typical of extraintestinal pathogenic E. coli (ExPEC), and that they exhibit a diffusely adherent pattern of adherence with Hep-2 cells, thus having many of the features of uropathogenic E. coli (UPEC).…”
Section: Introductionmentioning
confidence: 99%